Comparative analysis of men's and women's attack in Estonian volleyball championship league - Stamm, R.; Stamm, M.; Torilo, D.; Jairus, A. (21st Annual Congress of the European College of Sport Science (ECSS), Vienna, 6. -9. July 2016, 2016)
Introduction: Do the attack tactics of men and women in the highest volleyball league of Estonia differ and how? Which is the tempo of attack and are more spikes or decoys used, and what is the efficiency of different types of attack in men`s and women`s games? Methods: A total of 20 videos of men`s and women`s championship games of 2014/2015 were analysed, and the tempos and types of attacks were registered. The assessment of the tempo of attack was based on Selinger`s classification which uses three categories: tempo 3 — a slow tempo when the attacker begins the steps of approach when the set ball has reached the highest point of its flight trajectory; tempo 2 — a medium tempo, the attacker begins the steps of approach when the ball has left the setter`s hands, and tempo 1 — a quick tempo where the attacker performs the approaching steps before the setter touches the ball (Selinger, 1986). To determine the type of attack the distinction between vigorous attack and set attack or decoy was used. Data Volley and Volleysoft 6-3 statistics programs were used to estimate the efficiency of attack. Multinominal logistic regression was applied to analyse the attack actions that could differentate male and female game profiles. Results: The difference between men and women appears in tempo 3 and tempo 1, as men use tempo 3 or the slow attack least of all the tempos of attack (11.2%), which refers to the faster attack action in men`s games and to the tendency to attack against one blocker or against a block with a hole in it. In women, however, tempo 3 attacks were more frequent than tempo 1 attacks. The results of regression analysis showed that in men`s teams the opportunity to perform a tempo 1 attack compared to tempo 3 was 1.48 times greater than in the case of women. In the case of tempo 2 attack compared to tempo 3, in men the potential performance of tempo 2 is 1.8 times greater than in women (p<0.05). The analysis of attack types revealed that both men and women use vigorous attacks in games more often than decoys. The difference between men and women lies in the relation between using the decoy and the spike. Women use the decoy in games 8% more than men do. Discussion: Women`s attack activity had lower proficiency than men`s. Men gained a point from 46.2% of attacks, women — from 36.2%. For comparison, men`s mean result in World Championship games in 2011 was 50.2% and in Brazilian women`s Super League in 2012 38.7% (Costa, 2014). In conclusion, it can be said that in Estonian men`s championship games tempo 1 attacks are used statistically significantly more often than in women`s games. Men are more proficient at attack and use vigorous spike more often than women do.